2019
DOI: 10.1101/734137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What difference do retractions make? An estimate of the epistemic impact of retractions on recent meta-analyses

Abstract: Every year, several hundred publications are retracted due to fabrication and falsification of data or plagiarism and other breeches of research integrity and ethics. Despite considerable research on this phenomenon, the extent to which a retraction requires revising previous scientific estimates and beliefs – which we define as the epistemic impact - is unknown. We collected a representative sample of recently retracted studies that had been included in recent meta-analyses, and compared the summary effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the case of Fujii’s extensive publications, the effect of his misconduct on the management of postoperative nausea and vomiting appears to have only been minimised by the large volume of publications from other authors 79. In a recent paper, analyses by Fanelli and Moher92 suggested that meta-analyses may overestimate their summary effect sizes when they include studies later retracted for issues with data, methods or results.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Fujii’s extensive publications, the effect of his misconduct on the management of postoperative nausea and vomiting appears to have only been minimised by the large volume of publications from other authors 79. In a recent paper, analyses by Fanelli and Moher92 suggested that meta-analyses may overestimate their summary effect sizes when they include studies later retracted for issues with data, methods or results.…”
Section: Discussionmentioning
confidence: 99%
“…These results align well with literature on case studies [7,8], specific disciplines [9] and the broader literature [10], which identify that at least 80% of retracted articles receive positive post-retraction citations. Such perpetuated misinformation is not inconsequential: guidelines and meta-analyses seem to be very rarely updated to remove retracted articles [11] and a recent preprint suggests that doing so would lead to a median reduction in estimated effect size of 13% and an average reduction of 30% [12].…”
Section: Introductionmentioning
confidence: 99%
“…The retraction was for misappropriation of ideas and text from a paragraph of a manuscript that was undergoing review ( 50, 51 ). The case is provocative, as the “epistemic impact” ( 52 ) of the retraction seems minor. But the problem has broad ethical dimensions framing the relationship among authors, reviewers and editors ( 51 ).…”
Section: Resultsmentioning
confidence: 99%